THE IMPACT OF GAMES ON THE DEVELOPMENT OF PRE-SCHOOL CHILDREN (Scientific journal of the Fergana State University, 2024)
This article analyzed the literature on the role of play in the child’s life in the all-round development of children. Play activities are the basis of preschool children's life. Because all the serious work that children do is manifested in the form of play. We can observe positive features in children's development when ensuring the integral connection of play activities with work and education in the development of children.